Pemimpin Negara dalam Perspektif Hadis-Hadis Siyasah: Analisis Hadis Quraisy dan Non-Quraisy dalam Kaitannya dengan Konteks Kepemimpinan di Indonesia - Aripin Marpaung (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study stems from a classic question in the study of political hadith regarding leadership, specifically the hadith "The Imams are from Quraysh," which is often understood textually as requiring leaders to be from the Quraysh tribe. This kind of understanding often stops at the normative and historical level, without considering the socio-political context of modern society, which is fundamentally different from the early Islamic era. As a result, a gap emerged between the moral message of the hadith and the reality of the leadership system in democratic countries like Indonesia. This research aims to reanalyse the meaning of hadiths about Quraysh and non-Quraysh leadership, and to trace their relevance to the concept of state leadership in the Indonesian constitutional system, placing Islamic political theory and modern leadership theory on an equal footing (theory = theory). This research employs a qualitative approach based on library research, with the primary sources being political hadiths and classical references such as al-Ahkam al-Sulthaniyyah by al-Mawardi, supplemented by contemporary literature on the modern Indonesian government system. The analysis was conducted using comparative methods and content analysis to explore the commonalities and differences between the concept of Imamah in Islam and leadership in modern democratic systems. The research findings indicate that the hadith about Quraysh leadership cannot be understood rigidly as a limitation of lineage, but rather as an ethical guideline emphasising the principles of justice, trust, responsibility, and public interest. The ethical values in the hadith align with the basic principles of the presidential system in Indonesia, such as public accountability, limitation of power, and popular sovereignty, as regulated in the 1945 Constitution. Despite challenges such as corruption, the politicisation of religion, and weak leadership morality, the values of the hadith remain relevant if translated into public norms and modern governance practices. This research confirms that leadership in Islam and Indonesian democracy can complement each other, with Islam providing a moral and spiritual foundation, while democracy offers the legal and political structure to realise it.